Venture capital, private equity, and the financing of entrepreneurship : the power of active investing - 219300 Lerner, Joshua; Leamon, Ann; Hardymon, G. Felda (Hoboken, NJ : John Wiley & Sons)
"Venture Capital, Private Equity, and the Financing of Entrepreneurship explores the exciting world of active investing and lays out in a clear and readily accessible way their key features, ways of doing business and likely evolution. The book follows the cycle of active investing. Raising funds, considering transactions, structuring and overseeing transactions, and exiting investments are considered in turn. The focus is not just on the U.S. market, but on the increasingly global nature of these activities"--Provided by publisher.